2021
DOI: 10.1177/09732179211019905
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels and Early Onset Sepsis in Newborns

Abstract: Aim: To find out association between vitamin D level and early onset neonatal sepsis (EONS). Methods: This case control study was conducted at a tertiary care center in Northern India during June 2018 to May 2019. Neonates with culture-proven EONS were included as case and neonates without EONS were enrolled as control. 25OH-D levels were evaluated with other routine blood samples. Statistical analysis was done by using unpaired t test and chi-square test. Results: Sixty-two infants were enrolled in each group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Additionally, Soliman et al observed that vitamin D, at a cutoff point of 18.75 ng/ml, had a 100% sensitivity, and 80% specificity for the diagnosis of newborn sepsis [ 26 ]. Another case–control study which recruited sixty-two infants with EOS and the same number as a control group, revealed that vitamin D levels were considerably lower in EOS with a cutoff value of 25 ng/ml, 88.7% sensitivity, and 79% specificity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Soliman et al observed that vitamin D, at a cutoff point of 18.75 ng/ml, had a 100% sensitivity, and 80% specificity for the diagnosis of newborn sepsis [ 26 ]. Another case–control study which recruited sixty-two infants with EOS and the same number as a control group, revealed that vitamin D levels were considerably lower in EOS with a cutoff value of 25 ng/ml, 88.7% sensitivity, and 79% specificity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D levels may have an impact on the production of immunoglobulins, T cell lymphocyte activation, killer and T helper cell differentiation, neutrophil migration, and the production of antimicrobial peptides. Moreover, cord-blood 25-hydroxyvitamin D low levels have been related to the risk of early-onset neonatal sepsis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%